Teaching Computer Assisted Audit Tools and Techniques’ Courses: lessons learned - Pedrosa, I.; Costa, C. (Global Management Conference 2013, 2013)
Individual contexts on information technology acceptance have been a relevant research topic in recent years. Understanding the motivations and identifying the expectations that have impact on information technology or information system individual acceptance has been a worldwide research field for Information systems’ research groups. Performance and effort expectancy, social influence and facilitating conditions are the main determinants in individual information technology acceptance models. On facilitating conditions, formal courses attendance on computer assisted audit tools and techniques, CAATTs, can have a positive influence on intention to use/use an information system or technology. Then, 5 students groups, on an Auditing master course and for a period of 5 years, were asked to participate on this research bearing in mind a future and global pedagogical strategy to learn CAATTs which will be in line with the labour market needs on this core area. Indicators were measured and assessed, namely, the determinants on individual acceptance, students’ individual assessment on the core competences of the course and their individual scores on the most relevant topics presented. Those indicators are stated and discussed bearing in mind a global pedagogical strategy based on students’ individual opinions and assessment on the main aims of the course and lessons learned during this 5 years.